Pendampingan Untuk Menyusun Modul Ajar Kurikulum Merdeka - Yazidul Busthomi; Luqman Hakim (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2024)
Community service activities are activities carried out by lecturers in order to be one of the pillars of the tri dharma of higher education. Community service is one of the pillars of the tri dharma of higher education, in addition to the dharma of education and the dharma of research. The tri dharma of higher education, namely: education, research, and community service. Community service is an integral part of the tri dharma of higher education which in its implementation cannot be separated from the other two dharmas. Through community service, lecturers are present in the midst of the Indonesian nation. So in relation to community service from the Al-Qolam University campus, lecturers are entrusted with a task, namely mentoring to compile the independent curriculum teaching module at SMP Plus Al-Falah Al-Makky Putat Lor Gondanglegi Malang. The implementation of the community service is as follows: 1. Determining the mentoring staff at SMP Plus Al-Falah Al-Makky, 2. Determining the mentoring schedule at SMP Plus Al-Falah Al-Makky, 3. Assisting in compiling teaching modules at SMP Plus Al-Falah Al-Makky, 4. Guiding all participants when the activity is carried out, 5. Providing motivation so that teachers at the SMP are diligent in compiling teaching modules.